Electrical Resistivity Imaging in Parts of Nandurbar District, Deccan Volcanic Province, Maharashtra, India - Khan, Tahama; Gupta, Gautam; Erram, Vinit C.; Baride, Arti; Baride, Mukund V. (My University, 2022)
Exploration of groundwater resources in basaltic hard-rock terrain has always remained a challenging task for hydrogeologists as the potential groundwater zones/recharge pockets in such areas are associated with differential weathering, anisotropy, heterogeneities, fractured and fissured geological features etc. The thickness of the weathered/fractured layer overlying the compact rocks in such terrain plays a vital role in groundwater prospects. Paucity of water in the semi-arid trap covered areas of north Maharashtra necessitated to locate sources of groundwater almost all over the region. This has driven hydrogeologists to determine the role of dykes in the occurrence, movement and storage of groundwater. The study area is situated in Nandurbar district of Maharashtra bordering Narmada-Tapi rift zone. Two-dimensional (2D) electrical resistivity imaging (ERI) was used to generate subsurface resistivity models for delineating the availability of groundwater in the dyke-infested basaltic region of Nandurbar. The available dug well/borehole lithology suggests that the top layer is comprised of red bole, laterite or black soil followed by weathered/fractured rock. Results from the 2D inverted models of resistivity variation with depth suggest the occurrence of aquifers mostly in weathered/fractured zones within the traps or beneath it. The resistivity models suggest that the northern part of the study area represents a promising aquifer zone with reasonable thickness of weathered formation.
Keywords: Groundwater Resources; Maharashtra; Deccan Volcanic Province; Electrical Resistivity Imaging; Nandurbar District; ERI